The Implementation of Flipped Classroom Model in Teaching English to Sapta Andika Junior High School Students in Academic Year 2019/2020 - Dewi, N. P. Sara Sintia; Padmadewi, N. N.; Santosa, M. Hery (LPPM Undiksha, 2021)
This research investigated (1) the implementation of Flipped Classroom for teaching English; (2) the students’ achievement; (3) the students’ opinion; and (4) the differences between the high and low achieving students’ opinion toward Flipped Classroom. There were 41 seventh grade students and one English teacher of the seventh grade investigated. In this research, interview, questionnaires and lesson plan analysis were analyzed using interactive model; meanwhile the post-test and high and low achieving students’ opinion given were statistically analyzed using SPSS 16. It was resulting that in implementing Flipped Classroom the teacher did several preparations and teaching procedures which differentiated the classroom activity and home activity; the students’ achievement was seen to be good; the students also perceived the learning positively; the differences among high and low achieving students’ opinion were not significantly seen. This research helps the teacher who wants to implement flipped classroom as a consideration in teaching.